EXPANDING INSTRUCTIONAL MODEL OF SOCIO AFFECTIVE STRATEGY FOR SPEAKING SKILL IN ISLAMIC INSTITUTION - Hayati Syafri (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
English speaking strategies are broadly conceptualized as cognitive, metacognitive, and socioaffective strategies where are consciously or unconsciously employedby the multilingual speakers in studying. Nevertheless, students rarely utilize socioaffective strategies in speaking that caused students are anxiety, less ability to socialize, less self-confidence and motivation that give the bad effect to the students as multilingual speakers on their speaking performance in the classroom. Meanwhile, the speaking lecturer who has use the modul of socio affective strategies in IAIN Bukittinggi still face some difficulties in applying it since the materials are not really appropriate to the culture of students in islamic institution. To solve these problems, there must be the expanding instructional model that is not only focus on the socio affective strategies in teaching English but also integrating the culture of local wisdom to the model. Consequenly, this studyidentify the strengths and weaknesses of  Socio affective in Feby’s model and develop Socio-cultural affective strategy model in speaking skill. After conducting R and D research, through Planning, Impementing and Evaluating Model (PIE model) to third semester students registered 2015/2016 academic year of English Department in the State of Islamic Religious Institute (IAIN) Bukittinggi in Indonesia, it is found that  socio cultural affective strategy model is effective to improve students’ speaking skill.